Access to Finance, Foreign Ownership, and Foreign Takeovers in Germany - John P. Weche Gelübcke; Joachim Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
With this paper we present the fi rst microeconometric analysis of the impact of a foreign acquisition on the target fi rms' access to fi nance. By using a large database of German firms we furthermore investigate for the first time the link between foreign ownership and access to finance in Germany, one of the world's leading target countries for foreign direct investment. We use newly available comprehensive panel data that we constructed from information collected by the German statistical offi ces and from credit rating scores supplied by the leading German credit rating agency. We find foreign owned firms in German manufacturing on average to show slightly more nancing restrictions than domestically owned enterprises, but this very small di fference diminishes once unobserved heterogeneity is taken into account. We further demonstrate that one reason for this finding is the preference of foreign investors for targets with relatively low credit-worthiness. Although the likelihood of a foreign acquisition appears to be correlated with credit rating, there is no impact of foreign takeovers on the credit constraints of the target fi rms ex post and therefore no support for the hypothesis that foreign takeovers ease financial frictions.
Keywords: F21; F23; G34; 330